Buccal injection of synthetic HPV long peptide vaccine induces local and systemic antigen-specific CD8+ T-cell immune responses and antitumor effects without adjuvant. Issue 1 (December 2016) - Yang, Ming-Chieh; Yang, Andrew; Qiu, Jin; Yang, Benjamin; He, Liangmei; Tsai, Ya-Chea; Jeang, Jessica; Wu, T.-C.; Hung, Chien-Fu
Abstract Background Human Papillomavirus is responsible for over 99 % of cervical cancers and is associated with cancers of the head and neck. The currently available prophylactic vaccines against HPV do not generate therapeutic effects against established HPV infections and associated lesions and disease. Thus, the need for a therapeutic vaccine capable of treating HPV-induced malignancies persists. Synthetic long peptides vaccination is a popular antigen delivery method because of its safety, stability, production feasibility, and its need to be processed by professional antigen presenting cells before it can be presented to cytotoxic CD8+ T lymphocytes. Cancers in the buccal mucosa have been shown to elicit cancer-related inflammations that are capable of recruiting inflammatory and immune cells to generate antitumor effects. In the current study, we evaluated the therapeutic potential of synthetic HPV long peptide vaccination in the absence of adjuvant in the TC-1 buccal tumor model. Result We show that intratumoral vaccination with E7 long peptide alone effectively controls buccal TC-1 tumors in mice. Furthermore, we observed an increase in systemic as well as local E7-specific CD8+ T cells in buccal tumor-bearing mice following the vaccination. Finally, we show that induction of immune responses against buccal tumors by intratumoral E7 long peptide vaccination is independent of CD4+ T cells, and that the phenomenon may be related to the unique environment associated with mucosal tissues. Conclusion Our results suggest the possibility for clinical translation of the administration of adjuvant free therapeutic long peptide vaccine as a potentially effective and safe strategy for mucosal HPV-associated tumor treatment.